Through-Thickness Residual Stresses, Microstructure, and Mechanical Properties of Electron Beam-Welded CA6NM Martensitic Stainless Steel after Postweld Heat Treatment - Sheida Sarafan; Priti Wanjara; Jean-Benoît Lévesque; Javad Gholipour; Henri Champliaud; Louis Mathieu (Advances in Materials Science and Engineering)
In this study, the integrity of electron beam- (EB-) welded CA6NM—a grade of 13% Cr-4% Ni martensitic stainless steel—was assessed through the entire joint thickness of 90 mm after postweld heat treatment (PWHT). The joints were characterized by examining the microstructure, residual stresses, global mechanical properties (static tensile, Charpy impact, and bend), and local properties (yield strength and strain at fracture) in the metallurgically modified regions of the EB welds. The applied PWHT tempered the “fresh” martensite present in the microstructure after welding, which reduced sufficiently the hardness (<280 HV) and residual stresses (<100 MPa) to meet the requirements for hydroelectric turbine assemblies. Also, the properties of the EB joints after PWHT passed the minimum acceptance criteria specified in ASME sections VIII and IX. Specifically, measurement of the global tensile properties indicated that the tensile strengths of the EB welds in the transverse and longitudinal directions were on the same order as that of the base metal (BM). Evaluation of the local tensile properties using a digital image correlation (DIC) methodology showed higher local yield strengths in the fusion zone (FZ) and heat-affected zone (HAZ) of 727 MPa and 740 MPa, respectively, relative to the BM value of 663 MPa. Also, the average impact energies for the FZ and HAZ were 63 J and 148 J, respectively, and attributed to the different failure mechanisms in the HAZ (dimples) versus the FZ (quasi-cleavage consisting of facets and dimples). This study shows that the application of PWHT plays an important role in improving the weld quality and performance of EB-welded CA6NM and provides the essential data for validating the design and manufacturing process for next-generation hydroelectric turbine products.